Răspunsuri

2014-05-06T22:23:47+03:00
A){2(x+y-1)+3=y                 {2x+2y-y-2+3=0       ⇒{2x+y=-1    inmultim cu -3
    {3(2x+1)-4y=0⇒             {6x+3-4y=0⇒              {6x-4y=-3

{-6x-3y=3
{6x-4y=-3⇒      -7y=0⇒    y=0
din 2x+y=-1⇒    2x+0=-1⇒     2x=-1⇒   x=-1/2

b)  {(x+1)/3-(y-2)4=1/6⇒ aducem la acelasi numitor care este 24⇒
     {x+y-3=0
{8x+8-6y+12=4⇒   {8x-6y=-16                              {8x-6y=-16
{x+y=3                    {x+y=3        inmultim cu 6⇒     {6x+6y=18⇒    14x=2
x=2/14 ⇒  x=1/7
din x+y=3 inlocuim⇒ 1/7+y=3⇒    y=3-1/7⇒    y=20/7